The compliance of specialized medical care of patients with glaucoma to clinical recommendations (CR 96/1 “Primary open-angle glaucoma”) in Russian Federation regions - V. V. Neroev; T. N. Malishevskaya; M. P. Kharlampidi; L. A. Mikhaylova; S. Yu. Petrov; A. V. Zolotarev; A. Zh. Fursova; G. V. Simonenko (Российский офтальмологический журнал)
The high prevalence of primary open-angle glaucoma, its leading role in the structure of visual disability, and insufficient effectiveness of treatment, prevention and rehabilitation measures require new approaches to providing quality care of patients with glaucoma. It is important to analyze the epidemiological situation, human and technological resources in various regions of the Russian Federation. The paper evaluates the compliance of specialized medical care of patients with glaucoma with the approved clinical guidelines CR 96 “Primary open-angle glaucoma” in the regions of the Russian Federation monitored by the Helmholtz National Research Center for Eye Diseases, based on the material of on-site data collection visits. The epidemiological situation relating to glaucoma, the structure and performance indicators of ophthalmological service departments, preventive measures, human and material resources, and the correctness of statistical accounting and reporting were studied. In most regions, the times of examination and treatment correspond to the regional territorial programs covered by state guarantees. The cases when primary specialized care lags behind is associated with staff shortage at the outpatient level. Practically in all regions of the Russian Federation, diagnostic methods and conservative/surgical treatment techniques with proven high efficiency conform to CR 96/1 “Primary open-angle glaucoma”. Some of the regions, however, are insufficiently equipped for early diagnosis of glaucoma and monitoring its course.